The effect of heparin prescription before primary PCI on long-term and short-term clinical and para clinical results and the mortality of patients with acute coronary syndrome - Zamani, Bijan; Abdollahi, Asghar; Mardi, Afrooz (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Primary PCI (PPCI) is the main reperfusion treatment for ST-segment elevation myocardial infarction (STEMI). Anticoagulation therapy should be administered in patients undergoing PCI in order to limit the ischemic complications. In this study, we evaluated the effect of bolus unfractionated heparin (UFH) before PPCI on clinical outcome of patients with STEMI. Methods: In this randomized clinical trial, 196 patients (72.4% male with mean age of 63.02±13.37 years) with STEMI undergoing PPCI were randomly assigned to receive bolus UFH 60-90 U/kg in emergency room (case group) or during PCI (control group). Clinical outcomes, 30 day mortality, hematoma, left ventricle function improvement during follow-up were compared between groups. Results: In both groups there was good flow in the involved coronary artery after PCI. Case group compared to control group had significantly more cases with improved LVEF (28.1% vs. 9.7%, p=0.005). Also, case group compared to control group had more hematoma (3.1% vs. 0%, p=0.24) and higher mortality rate (6% vs. 4.2%, p=0.56) which had no significant difference between groups. Conclusions: PPCI in patients with STEMI accompanies with acceptable coronary flow irrespective of receiving bolus heparin. Receiving bolus heparin in these patients may have improved left ventricle function by increasing the rate of reflow. However, using bolus heparin did not accompany with increased rate of bleeding and had no effect on 30 day mortality rate.